Do job creation schemes improve the social integration and well-being of the long-term unemployed? - Boris Ivanov; Friedhelm Pfeiffer; Laura Pohlan (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
In this paper we analyze the effects of a German job creation scheme (JCS) on the social integration and well-being of long-term unemployed individuals. Using linked survey and administrative data for participants and a group of matched non-participants, we find significant positive effects of being employed within this program. They are larger for individuals with health impairments and above-average duration of welfare dependence. The program effects decline over time, which cannot be explained by decreasing levels of well-being and social integration of the participants. Instead, this decrease is driven by a rising share of controls who find a job and catch up to similar outcome levels as program participants. Overall, our results suggest that JCSs can be an efficient labor market policy instrument to improve the quality of life of the long-term unemployed.
Keywords: I31; J64; 330; unemployment; active labor market policy; job creation schemes; wellbeing; social integration; matching